Occurance of Blastocystis sp in water catchments at Malay villages and Aboriginal settlement during wet and dry seasons in Peninsular Malaysia - Noradilah, SA; Lee, IL; Anuar, TS; Salleh, FM; Manap, SNAA; Mohtar, NSHM; Azrul, SM; Abdullah, WO; Moktar, N (Peerj Inc, 2024)
In the tropics, there are too few studies on isolation of Biastocystis sp. subtypes from water sources; in addition, there is also an absence of reported studies on the occurrence of Blastocystis sp. subtYPes In water during different seasons. Therefore, this stud)/ was aimed to determine the occurrence of Blastocystis sp. subtypes in river water and other water sources that drained aboriginal vicinity of highly endemic intestinal parasitic infections during wet and dry seasons. Water samples were collected from six sampling Points of Sungai Krau (K1-K6) and a Point at Sungai Lompat (K7) and ()the: water sources around the aboriginal villages. The water samples were collected during both seasons, wet and dry seasons. Filtration of the water samples were carried out using a flatbed membrane filtration system. The extracted DNA from concentrated water sediment was subjected to single round polymerase chain reaction and positive PCR products were subjected to sequencing. All samples were also subjected to filtration and cultured on membrane lactose glucuronide agar for the detection of faecal coliforms. During wet season, Blastocystis sp. ST1, ST2 and ST3 were detected in river water samples. Blastocystis sp. ST3 occurrence was sustained in the river water samples during dry season. However Blastocystis sp. ST1 and ST2 were absent during dry season. Water samples collected from various water sources showed contaminations of Blastocystis sp. ST1, ST2, ST3 and ST4, during wet season and Blastocystis sp. ST1, ST3, ST8 and ST10 during dry season. Water collected from all river sampling points during both seasons showed growth of Escherichia coli and Enterobacter aerogenes, indicating faecal contamination. In this study, Blastocystis sp. ST3 is suggested as the most resistant subtype able to survive in any adverse environmental condition. robust and Restriction and control of human and animal faecal contaminations to the river and other water